Study of the CTLA-4 gene polymorphisms in systemic lupus erythematosus (SLE) samples from Malaysia - Chua, K.H.; Puah, S.M.; Chew, C.H.; Tan, S.Y.; Lian, L.H. (2010)
In this study, we investigated the polymorphisms of the exon 1 (+49A/G), promoter sites (-1722T/C, -1661A/G, -318C/T), and 3'-untranslated region (3'-UTR) (+6230 A/G) of the CTLA-4 gene in systemic lupus erythematosus (SLE) affected patients. Polymerase chain reaction-restriction fragment length polymorphism was used to determine genotypes of these five markers in 130 SLE patients and 130 healthy controls. Of the five tested polymorphisms, there was no statistical significant difference between the genotypic and allelic frequencies of patients with SLE and controls. Hence, we propose that the CTLA-4 gene does not play a major role in the genetic susceptibility to the development of SLE in the Malaysian population.